Nitrogen-doped carbon-based phenolic resin loaded with Pd NPs for hydrodechlorination of 4-Chlorophenol - Zhengyu Pan; Xianlang Chen; Zijian Wang; Rongrong Li; Tongyang Song; Yuhao Cai; Deman Han; Jianrong Chen (Scientific Reports)
Abstract The catalytic hydrodechlorination (HDC) technology exhibits great flexibility and safety under mild conditions, and shows extremely promising application prospects for the degradation of 4-Chlorophenol (4-CP). Prepare the N-doped phenolic resin carbon support (PMF) using phenol, melamine and formaldehyde as raw materials, and load Pd nanoparticles (NPs) on it. The XPS results indicate that the Pd/PMF-800 has a higher Pyridine-N (24.8%) and a higher Pd0/(Pd2++Pd0) ratio (65.4%). Moreover, the difference in electronegativity between the N atom and the resin carbon support enhances the binding energy between them. This enhancement promotes the nucleation of Pd NPs on the surface of the resin carbon support, thereby imparting higher stability to the Pd NPs. Due to these comprehensive advantages, Pd/PMF-800 has the highest dechlorination activity (kobs = 0.0594 min⁻¹) and stability (dechlorination rate is 91.56% after 5 cycle). Additionally, it also demonstrates efficient dehalogenation rates for 2-Chlorophenol and 4-Bromophenol. It can provide a catalyst that has high-efficiency dehalogenation performance, strong acid and alkali stability and adaptability, and can be recycled for the degradation of halogenated phenols in the environment.